Fine Art Gallery in Bandung with Contemporary Architecture Approach - Wima Alkad Albadira; Andiyan Andiyan; Fajar Ikhwan Harnomo (Jurnal Arsitektur Archicentre, 2023)
Bandung is one of the most creative cities in Indonesia. Many creative communities exist in the city of Bandung, Bandung has a lot of creativity and was chosen as an Asia Pacific creative city pilot project. The success of developing Bandung's image as a creative city depends heavily on the people available, and the creative community. Based on Presidential Regulation Number 72 of 2015 Fine Arts is one of the government policies, in launching the Strategic plan (Renstra) requires a place for artists and art lovers in the form of facilities such as art galleries. With the existence of art galleries as additional art facilities and infrastructure, it is hoped that they can be a driver of the development of the creative economy of art and at the same time contribute to providing a forum for artists and art lovers/observers in the city of Bandung. The application of the characteristics of contemporary architecture from the application system of slender materials on the facade, the application of subtractive and addictive forms, solid building forms, landscape elements, and interconnected buildings will be implemented in the design of the art gallery building. The method used is a descriptive qualitative method using field surveys and searching for literature/precedent studies that will be used as a reference in the design and making comparative studies of similar functions and themes. The concepts in the design that will be discussed are the space program, the basic concept, the site concept, the building mass concept, the building zoning concept, the building circulation concept, the structural concept, and the utility concept. This design is expected to be a useful design picture and can be developed again in the future.